Phycocyanin/lysozyme nanocomplexes to stabilize Pickering emulsions for fucoxanthin encapsulation - Bai, Y.; Sun, Y.; Li, X.; Ren, J.; Sun, C.; Chen, X.; Qi, H.
Food-grade Pickering emulsions with plant proteins have attracted increasing interest in recent years. In this work, we report a type of phycocyanin (PC)electrostatic nanocomplex fabricated following a complexation between PC and lysozyme (Lys). The aim was to investigate toward investigating the performance of phycocyanin-Lysozyme (PC-Lys)nanocomplexes in stabilizing Pickering emulsions and protecting fucoxanthin (FX)from degradation. The properties of the PC-Lys nanocomplexes were characterized by 1H nuclear magnetic resonance (NMR)spectroscopy and three-phase contact angle. Using PC-Lys nanocomplexes as emulsifiers, Pickering emulsions were successfully prepared. Pickering emulsions stabilized by PC-Lys nanocomplexes generated a tight three-dimensional network structure, which increased the memory modulus and viscoelasticity of the emulsion. Furthermore, the produced Pickering emulsions considerably increased the chemical stability and bioavailability of FX. Overall, our study showed that PC-Lys nanocomplexes have the potential for use in Pickering emulsion construction with enhanced protective effects on loaded lipophilic ingredients.
Keywords: PHYCOCYANIN; LYSOZYME; NANOCOMPLEXES; FUCOXANTHIN; BIOAVAILABILITY